Can Africa Export Manufactures? : The Role of Endowment, Exchange Rates, and Transaction Costs - Elbadawi, A. Ibrahim (The World Bank, 1999)
May 1999 - Africa's poor performance in manufactured exports in the 1990s (relative to East Asia) appears to be largely the result of bad policies-especially policies that affect transaction costs. Elbadawi analyzes the determinants of manufactured exports in Africa and other developing countries, guided by three pivotal views on Sub-Saharan Africa's (Africa's) prospects in manufactured exports: ° Adrian Woods holds that Africa cannot have comparative advantage in exports of labor-intensive manufactures (even if broadly defined to include raw material processing) because its natural resources endowment is greater than its human resources endowment (endowment thesis). ° Paul Collier argues that, for most of Africa, unusually high (policy-induced) transaction costs are the main source of Africa's comparative disadvantage in manufactured exports (transaction thesis). ° A third approach (Elbadawi and Helleiner) emphasizes the importance of stable, competitive real exchange rates for profitability of exports in low-income countries (exchange rate-led strategy). Elbadawi tests the implications of these three views with an empirical model of manufactured export performance (manufactured exports' share of GDP), using a panel of 41 countries for 1980-95. His findings: ° Corroborate the predictions of the transaction thesis, in that transaction costs are major determinants of manufactures exports. Investing in reducing these costs generates the highest payoff for export capacity. ° Lend support for the exchange rate-led strategy.